Distance students in agricultural and coastal regions of Costa Rica: socio-demographic characteristics, preferences and access to technologies (UNED Research Journal, 2018)
Costa Rica is one of the Latin American countries with the longest history in distance education, through the Distance State University, UNED, so it is of general interest to know its students and their relationship with technology and education. To assess these characteristics, we applied questionnaires to 66 students from an agricultural and livestock community (Sarapiquí) and 216 from a port community (Puntarenas). They reported a good level of access to electronic devices and Internet; prefer hybrid courses and like the coexistence of varied media and didactic materials. Even though they have a reduced participation in the groups that UNED offers them, they consider participation to be important in the process of professional formation.
Keywords: distance education; student profile; information and communication technologies; student participation and communication; media and didactic materials